A New Presentation: Aphallia, Vesicoureteral Reflux, Rectovesical Fistula, and Adrenal Insufficiency - R. El Qadiry; A. Lalaoui; H. Nassih; A. Bourrahouat; I. Ait Sab (Case Reports in Pediatrics)
Aphallia or penile agenesis is a rare congenital malformation with an estimated incidence rate of 1 in 10 to 30 million births. More than half of aphallia cases have associated anomalies including caudal axis, cardiovascular, genitourinary, and gastrointestinal anomalies. The penile agenesis associated with adrenal insufficiency has never been reported in an infant. We report a rare case of a newborn that was diagnosed as a case of aphallia with vesicorectal fistula and vesicoureteral reflux, complicated by adrenal insufficiency with salt-wasting crisis.